Deferred statistical convergence and strongly deferred summable functions - Et, Mikail; Baliarsingh, P.; Sengul, Hacer (Amer Inst Physics, 2019)
The main purpose of this paper is to introduce and investigate the concepts of deferred strong summability and deferred statistical convergence of real-valued functions which are measurable (in the Lebesgue sense) in the interval (1,infinity). Some relations between deferred strong summability and deferred statistical convergence of real-valued functions which are measurable (in the Lebesgue sense) in the interval (1,infinity) are also given.
3rd International Conference of Mathematical Sciences (ICMS) -- SEP 04-08, 2019 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Sequences; series; summability; functional analysis